A novel online method for locating fault coil in direct‐drive permanent magnet synchronous motor with inter‐turn short‐circuit fault using search coil array - Chen, Hao; Zhang, Nan; Gao, Caixia; Xu, Xiaozhuo; Feng, Haichao; Si, Jikai; Hu, Yihua (IET electric power applications, 2023)
This study presents a fault coil localisation approach for a direct‐drive permanent magnet synchronous motor (DDPMSM) with inter‐turn short‐circuit fault (ISF) using the search coil (SC) array. The SCs are wound around specific stator tooth of DDPMSM through the proposed SC array arrangement principle, which reduces the invasiveness of the fault coil localisation method. The SCs are classified as several search coil groups (SCGs), the differential between SC back electromotive forces (EMFs) in the same SCGs (δ1) and SC residual back EMF (δ2) are used as fault indicators for ISF localisation. The peak values extracted from δ1 and δ2 are the basis for diagnosing ISF. Hence, the proposed approach does not need a complicated signal processing algorithm, and it is less complex. First, the SC back EMF analytical model is developed to investigate the mapping relationship between the back EMF of each SC and fault coil location. Second, fault coil localisation indicators for ISF are analysed based on the proposed analytical model, and the exact ISF localisation approach is presented. Finally, two basic installation units and the arrangement principle of SC array in DDPMSM are proposed. Simulation and experimental results justify the effectiveness of the selected fault indicators and the feasibility of the proposed SC array for diagnosing ISF. This paper presents a fault coil localization approach for direct‐drive permanent magnet synchronous motor (DDPMSM) with inter‐turn short‐circuit fault (ISF) using the search coil (SC) array. The SCs are wound around specify stator tooth of DDPMSM through the proposed SC array arrangement principle, which reduces the invasiveness of fault coil localization method.Compared with the existing methods based on SCs wound around each tooth in motor, the proposed method is more sensitive and accurate.